2019
DOI: 10.1021/acs.jpcb.9b05866
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Coupled Redox-Linked Conformational Switching at the Active Site of the Non-Heme Iron-Dependent Dioxygenase, TauD

Abstract: 2-Oxoglutarate (2OG)-dependent dioxygenases catalyze C−H activation while performing a wide range of chemical transformations. In contrast to their heme analogues, non-heme iron centers afford greater structural flexibility with important implications for their diverse catalytic mechanisms. We characterize an in situ structural model of the putative transient ferric intermediate of 2OG:taurine dioxygenase (TauD) by using a combination of spectroelectrochemical and semiempirical computational methods, demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 48 publications
(150 reference statements)
3
16
0
Order By: Relevance
“…Following that phase are multiple slower kinetic phases, which cannot be limited by the bimolecular rate and, therefore, are attributed to the changes in the properties of the protein. This behavior contrasts with a simple, monophasic oxidation of ferrous Mb by FCN, 11 or the reduction of ferric myoglobin (Mb) by thionine acetate (TA, Figure S3, left), as expected for a sample with reversible electrochemical behavior. Reactions with Mb quickly reach a redox equilibrium that corresponds to a E 1/2 of −155 mV, in good agreement with the reported value of −153 mV 17 and show little change after the first 5 s. The lack of change in the extent of oxidation of TA by Mb confirms that the sample remains anaerobic over a 1 h measurement and that gradual changes observed in TauD are not due to a slow ingress of atmospheric O 2 .…”
Section: ■ Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Following that phase are multiple slower kinetic phases, which cannot be limited by the bimolecular rate and, therefore, are attributed to the changes in the properties of the protein. This behavior contrasts with a simple, monophasic oxidation of ferrous Mb by FCN, 11 or the reduction of ferric myoglobin (Mb) by thionine acetate (TA, Figure S3, left), as expected for a sample with reversible electrochemical behavior. Reactions with Mb quickly reach a redox equilibrium that corresponds to a E 1/2 of −155 mV, in good agreement with the reported value of −153 mV 17 and show little change after the first 5 s. The lack of change in the extent of oxidation of TA by Mb confirms that the sample remains anaerobic over a 1 h measurement and that gradual changes observed in TauD are not due to a slow ingress of atmospheric O 2 .…”
Section: ■ Resultsmentioning
confidence: 80%
“…These features were previously proposed to arise from redox-linked peptide backbone reorganization. 11 Several other vibrations were assigned to individual metal ligands. The complete loss of the 1558 cm −1 mode in the H99A variant and its retention in the D101Q variant suggest that it arises from the imidazole CC stretching vibration.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar approach was later used in the analysis of Raman spectra of methane monooxygenase (Banerjee, Proshlyakov, Lipscomb, & Proshlyakov, 2015). In more recent studies, it was used to obtain completely unknown difference spectra of a redox transition with an unknown potential over a variable polynomial background John, Swain, Hausinger, & Proshlyakov, 2019). In this case, analysis involved two orthogonal parametric vectors (frequency-dependent amplitudes vs. potential-dependent populations).…”
Section: Conceptmentioning
confidence: 99%
“…Therefore, it can be used to predict experimental data and to test proposed reaction mechanisms in most chemical processes controlled by a combination of kinetics and thermodynamics. These abilities have recently been demonstrated in a study of how electrochemical mediators affect the observed electrochemical properties of an analyte John, Swain, Hausinger, & Proshlyakov, 2019).…”
mentioning
confidence: 96%